Association between Thyroid Cancer and CTLA-4 Gene Polymorphisms: Association Between Thyroid Cancer and CTLA-4 - Sun, Liping; Niu, Tianfeng; Zhang, Yi (Cellular and Molecular Biology, 2023)
The study aimed to explore the relationship between cytotoxic T lymphocyte associate protein-4 (CTLA-4) gene polymorphisms and the onset of thyroid cancer. 200 patients with thyroid cancer were included in the disease group and 200 healthy people were selected as the control group (all of them were admitted to Huashan Hospital (East) of Fudan University). The peripheral blood was collected in both groups, and the polymorphic regions at CTLA-4 gene loci rs3087243 (G>A), rs606231417 (C>T) and rs1553657430 (C>A) were amplified via polymerase chain reaction (PCR). The expression level of the CTLA-4 gene was detected via RT-qPCR. Moreover, the associations of clinical indexes with CTLA-4 genotypes were analyzed. The G allele frequency at CTLA-4 gene locus rs3087243 was raised in the disease group (p=0.000). The frequencies of the GG genotype at rs3087243, TT genotype at rs606231417 and CA genotype at rs1553657430were decreased in the control group (p<0.001, p<0.001, p=0.002). The GA+AAfrequency at rs3087243 and CC+CTfrequency at rs606231417 in the disease group were lower than those in the control group. The linkage disequilibrium was higher at rs606231417 and rs1553657430(D'=0.431). Moreover, the CTLA-4 gene expression was remarkably raised in patients with CC genotype at rs1553657430than that in other genotype patients (p<0.05). The genotype at rs606231417was significantly associated with the calcitonin level in thyroid cancer patients (p=0.039), while the genotype at rs3087243 was significantly associated with the thyroid-stimulating hormone level in thyroid cancer patients (p=0.002).CTLA-4 gene polymorphisms have a significant association with the progression of thyroid cancer, which may be a susceptible factor for it.